The influence of the Guadalquivir river on spatio-temporal variability in the pelagic ecosystem of the eastern Gulf of Cádiz - CABALLERO, I.; MORRIS, E. P.; PIETRO, L.; NAVARRO, G. (Mediterranean Marine Science, 2014)
This study examines the spatio-temporal variability of the turbidity plume and phytoplankton biomass (in terms of chlorophyll) in the marine region influenced by the Guadalquivir estuary using ocean colour images over a period of 11 years (2003-2013). The area of the turbidity plume was calculated using water-leaving radiance at 555 nm (nLw555). Climatologic and monthly averages showed recurrent high nLw555 levels in winter and high chlorophyll in spring. Similar variability was confirmed by Empirical Orthogonal Function (EOF) analysis of 8-day composite images, illustrating the existence of different regions with similar behavior. The first EOF mode explained 60.7% and 31% of the variability in nLw555 and chlorophyll, respectively, and was associated with enhanced Total Suspended Solids (TSS) in autumn-winter and phytoplankton blooms in winter-spring periods. The results confirmed that the development of the turbidity plume and subsequent phytoplankton blooms were strongly regulated by river discharges and precipitation. Indeed, interannual variation in nLw555 was consistent with changes in the large-scale climate index, the North Atlantic Oscillation, a proxy for regional rainfall patterns. In the case of phytoplankton biomass, the second EOF mode revealed differentiation between offshore and nearshore areas, the latter characterized by delayed development of phytoplankton bloom due to light limitation by high TSS. This suggests that the stability of the water column, via its influence on phytoplankton light-limitation, influenced also the timing and magnitude of phytoplankton bloom events. The dynamic of the Guadalquivir estuary turbidity plume is a crucial factor for the pelagic ecosystem of the Eastern Gulf of Cadiz, governing phytoplankton productivity.